2005
DOI: 10.1182/blood.v106.11.753.753
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Central Quality Assurance Review Prior to Radiation Therapy on Protocol Compliance: POG 9426, a Trial in Pediatric Hodgkin’s Disease.

Abstract: Introduction. To reduce protocol non-compliance as a confounding variable impacting trial outcome, Pediatric Oncology Group (POG) mandated pre-radiation quality assurance review in POG 9426, a trial in pediatric early stage Hodgkin’s disease (HD). This report documents the impact of this quality assurance program. Patients and Methods. POG 9426 investigated response-based therapy in Stages IA, IIA, and IIIA1 HD without large mediastinal masses. Early complete responders to 2 cycles of ABVE recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This is reflected in the usage reported in this study in the suggested RCR sites such as Non/Hodgkin's lymphoma; gynaecological disease sites; prostate; parotid and rectum, proposing that these sites should now have a definitive recommendation for IVC. There was a similar compliance in department IVC practice between the recommended and suggested RCR sites, this is also in line with the UK findings [32]. Sites where IVC was commonly given but not recommended or suggested in the RCR guidelines include prostate, brain and paranasal sinuses.…”
Section: Discussionsupporting
confidence: 81%
“…This is reflected in the usage reported in this study in the suggested RCR sites such as Non/Hodgkin's lymphoma; gynaecological disease sites; prostate; parotid and rectum, proposing that these sites should now have a definitive recommendation for IVC. There was a similar compliance in department IVC practice between the recommended and suggested RCR sites, this is also in line with the UK findings [32]. Sites where IVC was commonly given but not recommended or suggested in the RCR guidelines include prostate, brain and paranasal sinuses.…”
Section: Discussionsupporting
confidence: 81%
“…However, the images at presentation and response were collected by QARC to (1) confirm response and (2) define radiation therapy treatment fields. The images were reviewed retrospectively for response confirmation and the central review agreed only 50% of the time with the site assessment, demonstrating the need to define response in a consistent manner if clinical trials were going to be designed to either titrate or augment therapy based on response to treatment [6].…”
Section: Problems In Clinical Trial Interpretation 31 Hodgkin Lymphomamentioning
confidence: 99%
“…The goal of modern radiation therapy is to secure the initial response to therapy, offer definitive therapy to appropriate patients, and provide safe and effective care to minimize risk of acute and long-term sequelae of management. In this manuscript we provide examples of how modern therapy can be safely applied and integrated with systemic management for clinical care (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). The goal of this paper is to demonstrate the process improvements in normal tissue sparing with modern radiation therapy to further promote the use of radiation therapy in the management of patients with lymphoma.…”
Section: Introductionmentioning
confidence: 99%